Trends in Sustainable Banking Practices: A Bibliometric Review of Green Financial Services and Risk Management Strategies - Judijanto, Loso; Mokodenseho, Sabil; Mokodompit, Abdul Tiar; Mamonto, Magfira; Lantong, Siti Madina (Jurnal Multidisiplin West Science, 2024)
Sustainable banking practices and environmentally friendly financial services are becoming an increasing research focus in the modern financial era. This article performs a bibliometric review of trends and strategies in this domain. It was found that green finance concepts, such as green bonds and environmentally friendly banking practices, as well as the integration of financial technology (fintech), were in the main spotlight. However, the COVID-19 pandemic has also influenced green investment trends and environmental risk management strategies. In conclusion, this article highlights future challenges and opportunities, including the integration of fintech in green finance, green banking practices in various countries, and the contribution of the financial sector to achieving the Sustainable Development Goals (SDGs).